Status report of the baseline collimation system of CLIC. Part I - Resta-Lopez, J; Angal-Kalinin, D; Dalena, B; Fernandez-Hernando, J; Jackson, F; Schulte, D; Seryi, A; Tomas, R (2011)
Important efforts have recently been dedicated to the characterisation and improvement of the design of the post-linac collimation system of the Compact Linear Collider (CLIC). This system consists of two sections: one dedicated to the collimation of off-energy particles and another one for betatron collimation. The energy collimation system is further conceived as protection system against damage by errant beams. In this respect, special attention is paid to the optimisation of the energy collimator design. The material and the physical parameters of the energy collimators are selected to withstand the impact of an entire bunch train. Concerning the betatron collimation section, different aspects of the design have been optimised: the transverse collimation depths have been recalculated in order to reduce the collimator wakefield effects while maintaining a good efficiency in cleaning the undesired beam halo; the geometric design of the spoilers has been reviewed to minimise wakefields; in addition, the optics design has been optimised to improve the collimation efficiency. This report presents the current status of the the post-linac collimation system of CLIC. Part I of this report is dedicated to the study of the CLIC energy collimation system.